Medical students' perceptions of the educational environment in a private medical school in southwest Nigeria - Oluwatosin O Oguntoye (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The educational environment plays a very important role in determining the overall performance of students. The aim of this study is to determine the perceptions of undergraduate medical students about their educational environment in a Nigerian university. MATERIALS AND METHODS: This was an observational, cross-sectional study conducted among final-year (600 level) undergraduate medical students. The Dundee Ready Education Environment Measure (DREEM) questionnaire was used for the study to assess the educational environment of the medical students. RESULTS: A total number of 100 final-year (600 level) undergraduate medical students participated in the study, out of which 27 (27.0%) were males and 73 (73.0%) were females with a male-to-female ratio of 0.37 to 1. The age range of the respondents was 21-30 years with a mean (±SD) of 23.54 (±1.403). The total mean DREEM score was 116.2/200. The total score of SPL domain was 30.2/48 (62.9%). The total score of SPT domain was 27.3/44 (62.0%), while that of SASP was 19.2/32 (60.0%). The total score of SPA domain was 26.6/48 (55.4%) and that of SSP was 13.1/28 (46.8%). For the SPL, SPT, SASP, and SPA domains, the score was above 50%. However, for the SSP domain the score was less than 50%. CONCLUSIONS: The total mean DREEM score in this study was 116.2/200, more positives than negatives, with the students' social perspective having the least domain score. There is a need to provide adequate social support system for medical students in general and particularly for those who get stressed.